Impact assessment of groundnut research in Zimbabwe - Mazhangara, E.P.; Anandajayasekeram, P.; Mudhara, M.; Martella, D.; Murata, M. (CAB International, 2007)
Groundnut research in Zimbabwe dates back to the 1950s. Makulu Red is a long season variety and it was released to farmers in 1966. Following its release, a considerable amount of research was undertaken that led to the release of four improved long season varieties, five short season varieties and one medium season variety. The objective of this study was to assess the impact of groundnut research and extension in Zimbabwe over the period 1966-2000. The specific objectives were to describe and understand the groundnut production system, assess the socio-economic impact of groundnut research and complementary services. The study utilized primary and secondary data. A simple benefit-cost analysis approach (a derivative of the surplus approach) was used to calculate the rate of return to groundnut R&D investments. In addition to the rate of return analysis, a qualitative assessment of institutional, environmental and socio-cultural impacts of groundnut R&D investment was carried out.